Bromo‐ and extraterminal domain protein inhibition improves immunotherapy efficacy in hepatocellular carcinoma. Issue 10 (17th August 2020) - Liu, Chen; Miao, Xiaolong; Wang, Yao; Wen, Liang; Cheng, Xiawei; Kong, Deqiang; Zhao, Pengwei; Song, Dandan; Wang, Xinyi; Ding, Xianfeng; Xia, Hongguang; Wang, Weilin; et al.
Abstract: Hepatocellular carcinoma (HCC) represents the majority of liver cancer and is the fourth most common cause of cancer‐related death. Although advances in molecular targeted therapy have shown promise, none of these agents has yet demonstrated significant clinical benefit. Bromo‐ and extraterminal domain (BET) protein inhibitors have been considered potential therapeutic drugs for HCC but the biological activity remains unclear. This study found that BET protein inhibition did not effectively suppress the progression of HCC, using a transgenic HCC mouse model. Mechanistically, the BET protein inhibitor JQ1 upregulated the expression of programmed cell death‐ligand 1 (PD‐L1) on the plasma membrane in vivo and in vitro. Moreover, JQ1 enhanced the expression of Rab8A, which upregulated the expression of PD‐L1 on the plasma membrane. This study also showed that JQ1 combined with anti‐PD‐L1 Ab effectively suppressed HCC progression, and this benefit was obtained by enhancing the activation and cytotoxic capabilities of CD8 T cells. These results revealed the crucial role and regulation of BET protein inhibition on the expression of PD‐L1 in HCC. Thus, combining BET protein inhibition with immune checkpoint blockade offers an efficient therapeutic approach for HCC. Abstract : Treatment with JQ1 enhanced the expression of Rab8A, subsequently inducing programmed cell death‐ligand 1 (PD‐L1) expression on the plasma membrane of hepatocellular carcinoma (HCC), which sensitized the liver response to anti‐PD‐L1 blockade. Thus, a combined treatment of JQ1 and anti‐PD‐L1 Ab was an effective combination immunotherapy for HCC.